ObasCId: An Ontologically-Based Approach for Concern Identification and Classification - Parreira, Paulo Afonso; Penteado, Rosângela Aparecida Dellosso (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2016: Anais do X Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2016)
The Aspect-Oriented Requirements Engineering (AORE) area intends to provide more appropriate strategies for software concern identification, classification (as crosscutting or non-crosscutting) and modularization, in the early phases of software development cycle. A commonly reported issue about the existing AORE approaches is the lack of appropriate resources (guidelines, processes, catalogs, among others) to support software engineers during the concern identification and classification. This work aims to mitigate this issue by proposing: (i) a reference ontology for the software concerns domain, called O4C (Ontology for Concerns), and (ii) an ontologically-based approach for AORE, called ObasCId (Ontologically-based Concern Identification and Classification), that suggests the usage of catalogs of software concerns and a well-defined process for supporting software engineers to perform these activities in a more systematic way. An experimental study was performed on ObasCId and its results indicated that this approach may positively contribute for the concern identification and classification effectiveness without harming its execution time.